The clustering of voltage‐gated sodium channels in various excitable membranes. Issue 5 (10th January 2020) - Eshed‐Eisenbach, Yael; Peles, Elior
Abstract: In excitable membranes, the clustering of voltage‐gated sodium channels (VGSC) serves to enhance excitability at critical sites. The two most profoundly studied sites of channel clustering are the axon initial segment, where action potentials are generated and the node of Ranvier, where action potentials propagate along myelinated axons. The clustering of VGSC is found, however, in other highly excitable sites such as axonal terminals, postsynaptic membranes of dendrites and muscle fibers, and pre‐myelinated axons. In this review, different examples of axonal as well as non‐axonal clustering of VGSC are discussed and the underlying mechanisms are compared. Whether the clustering of channels is intrinsically or extrinsically induced, it depends on the submembranous actin‐based cytoskeleton that organizes these highly specialized membrane microdomains through specific adaptor proteins.